Composition of Three Zingiberaceae Essential Oils and Their Efficacy Against the Survivability of Cocoa Pod Borer, Conopomorpha cramerella (Snellen) Eggs - Bakar, Saripah; Latip, Siti Noor Hajjar Md; Awang, Alias; Zhang, Aijun (Journal of the Bangladesh Agricultural University, 2024)
The use of botanical extracts derived from potential plants is promising due to their target-specific, biodegradable, and can be implemented in insect management programs. This study was conducted to observe the potential of three Zingiberaceae essential oils; Lesser galanga, Alpinia galanga, Turmeric, Curcuma longa; and ginger, Zingiber officinale against the Cocoa pod borer, Conopomorpha cramerella (Lepidoptera: Gracillariidae) - the most devastating pest of cocoa in the Southeast Asia region. Bioassay on the C. cramerella eggs were performed using four different concentrations of EOs at 100, 200, 400, and 800 ppm. It is found that the A. galanga performed as the best EOs that can disrupt egg hatchability (0.025b ± 0.158), where only 0.03 eggs hatched and significantly different (p<0.05) with control (2.367a ± 0.928), where 2.37 eggs were successfully hatched. The concentration of EOs at 800 ppm was able to influence the penetration rate of pre-larva on the cocoa pod. During large cage observation, the mean of C. cramerella eggs were the highest at control (0.900a ± 1.029) and significantly different (p<0.05) with C. longa (0.150b ± 0.483), A. galanga (0.050 b ± 0.221) and Z. officinale (0.025 b ± 0.158). Higher concentrations (400 and 800 ppm) able to hinder C. cramerella from depositing eggs after cocoa pods were treated with treatments. The effect of Zingiberaceae EOs towards the egg hatchability may provide a foundation for their potential in managing C. cramerella in the future. J Bangladesh Agril Univ 19(1): 22–29, 2021 https://doi.org/10.5455/JBAU.36604